Hyperstability of the k-Cubic Functional Equation in Non-Archimedean Banach Spaces - Youssef Aribou; Mohamed Rossafi (Journal of Mathematics)
Using the fixed point approach, we investigate a general hyperstability results for the following k-cubic functional equations fkx+y+fkx−y=kfx+y+kfx−y+2kk2−1fx, where k is a fixed positive integer ≥2, in ultrametric Banach spaces.